O Processo de aquisição da leitura no contexto escolar por alfabetizandos considerados portadores de dificuldades de aprendizagem - Sara Mourao Monteiro (2007)
This thesis is part of the research field about learning difficulties during the literacy process. Its theme is the process of reading acquisition in the school context for literacy learners that possess learning difficulties. The problem, here presented was taken from the first observations made in the field: which difficulties the students present when reading the division of words through stress, in the didactic-pedagogic methodology that tries to develop the process of learning reading skills? What is its relevance in this context for the students learning process? Through these questions, we searched to find elements to understand the students difficulties in learning the reading skills for word division in a group of Second graders from a Public Elementary School in the Municipal Network of Belo Horizonte and in the didactic-pedagogic methodology that is trying to overcome these difficulties. In this study, we faced the learning difficulty strategies in public schools; the process of acquiring word division skills in students with learning disability; the didactic-pedagogic methodology that searches the development of reading skills process which can be concluded that: (i) the strategies to face the students difficulties in learning created by the educational policies and in the public schools of the countryside reinforce the teachers feeling about how many students from poor background are unable to learn the skills of the written language; (ii) the reading of a word division which structure does not correspond to a canonic standard, is guided by the analysis of the internal structure of a word , with this in mind we took as a reference the meaning of what children understand for as being a word division: a two letter compound formed of a vowel and a consonant; and, finally(iii) the current social context in the literacy learning requires definitions in the didactic pedagogic methodology capable of contributing, together with the teachers/literacy guides that work in schools, to build practical acts that can be connected to the complex environment that characterizes the learning process of written language skills by children in the society.